INITIAL GROWTH AND PHYSIOLOGICAL PARAMETERS OF ROMANIAN SWEET CHERRY CULTIVARS ON IP – C7 ROMANIAN DWARFING ROOTSTOCKS - G. C.Popescu; M.Popescu (Journal of Animal and Plant Sciences, 2015)
Grafting is widely used in horticulture to improve fruit crop production. The selection of rootstocks in the grafting process depends on soil conditions, local climatic and environmental resources. The objective of this research was to assess the growth and physiological behavior of different national sweet cherry varieties.  The cherry cultivars i.e. Radu, Maria, Bucium, and Daria were grafted on IP-C7 dwarf rootstocks. It is demonstrated that the IP-C7 Romanian rootstock is compatible with Romanian sweet cherry varieties and can be used successfully for the establishment of intensive cherry plantations. The evaluation of the rootstock - scion interactions showed graft compatibility between the studied sweet cherry cultivars and dwarfing rootstocks. Plant vigor, number of buds and photosynthetic capacity were influenced by the interaction between rootstock and scion. The lowest trunk cross sectional area (TCSA) determined by IP-C7 was recorded in Radu cultivars. The Maria sweet cherry cultivar was the most vigorous in terms of trunk cross sectional area and trunk circumference. Rootstock - scion interactions revealed different photosynthetic capacity. Assimilatory pigments were differently influenced in different rootstock - scion combinations. The rootstock - scion combination evaluated in this study may be useful to develop high-density orchards.
Keywords: dwarf rootstocks; photosynthesis; Prunusavium L.; trunk cross-sectional area